2009
DOI: 10.1063/1.3057818
|View full text |Cite
|
Sign up to set email alerts
|

Topology and elemental distribution in Co alloy:oxide perpendicular media

Abstract: This analytical electron microscopy study was performed to understand better the microstructure of CoCrPt: SiO 2 media. The topology of the magnetic Co alloy grains and the distribution of the elements in the thin films were of special interest. High angle annular dark field images revealed that many grains in the range 5-8 nm have a cavity in their center, observed by low mass-thickness contrast. Electron energy loss spectroscopy Co elemental mapping shows Co to be concentrated mainly in the grains with a dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[11][12][13] It has long been suggested that a Cr-rich CoCr grain boundary could result in a significant disruption of intergranular exchange coupling.…”
Section: ͑2͒mentioning
confidence: 99%
“…[11][12][13] It has long been suggested that a Cr-rich CoCr grain boundary could result in a significant disruption of intergranular exchange coupling.…”
Section: ͑2͒mentioning
confidence: 99%